Comparing Rule-Based Translation to Syntax Tree Diagram Translation - heri heryono (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Machine translation has developed more effectively to be specified as modern linguistics characterization. It indicates the formalization of translating process by machine within humanly approaching. Recently, in order to help people communicate indirectly through written, machine translation has its own system to break and match the codes through comprehensive database of words pocket. In linguistics perspective, machine translation always be assisted by its definite performance through derivative computational system. The problem appears when users need to translate ambiguous sentence from English to Bahasa Indonesia or vice versa. The paper used rule-based system which contains particular parts in order to run the process of translating; starts from tokenization, pre-processing, reordering and morphological process which lead to output accuracy. And used syntactic diagram translation, which was carried out manually by generating sentences into small units. The result of this research showed that RBS runs by standard linguistics system; and the output of translating refer to basic translation without giving any alternative translation nor meaning. While using syntactic diagram, there are possibility to get alternative result not only by linguistics features but also based on signification meaning of both translations. Those techniques run by considering linguistics features in order to help users to get translation output better.